Linking emotion regulation strategies to employee motivation: The mediating role of guanxi harmony in the Chinese context - Zhang, Wenpei; Guo, Shanshan; Liu, Jiashu; He, Ying; Song, Mengmeng; Chen, Lirong (Frontiers in Psychology, 2022)
This study examined the mediating role of guanxi harmony, a concept of interpersonal relationships specific to the Chinese context, between leaders' emotion regulation strategies and employee motivation. Data were drawn from 489 on-the-job MBA students with enough management experience from thirteen different types of cities in China. The study tested the model using hierarchical regression. The results showed that the reappraisal strategy was positively related to employee motivation and the suppression strategy was negatively related to employee motivation in the Chinese context. Guanxi harmony played a partially mediating role between reappraisal and employee motivation, and played a fully mediating role between suppression and employee motivation. These findings suggest that in the Chinese context, guanxi harmony between leaders and employees has a positive effect on employee motivation, and when leaders apply appropriate emotion regulation strategies, they can achieve guanxi harmony and promote employee motivation.